Evaluation Study and Results of Intelligent Pedagogical Agent-led Learning Scenarios in a Virtual World - Soliman, M.; Guetl, Christian (IEEE Institute of Electrical and Electronics Engineers, 2014)
The use of intelligent pedagogical agents (IPAs) has shown to provide positive learning results and new learning possibilities. The IPA has specific importance in immersive learning environments to enable 24/7 availability, offer a learning companion opportunity, and increase learner engagement. In that regard, a proof of concept prototype implementation of an intelligent pedagogical agent (IPA) in the Open Wonderland virtual world environment was created. This paper reports a qualitative evaluation study and experiment performed by a team of six experts in relevant areas of expertise. Those areas include cognitive science, computer science, e-education, and virtual worlds. The experiment studied key prototype components in relation to four learning scenarios with distributed control between the learner avatar and the pedagogical agent to answer questions relevant to their effect on learning attributes such as motivation, engagement, and the learning experience. Given the qualitative nature of the experiment, the paper also analyzes and reports results relevant to expert input of how the prototype can better contribute to future pedagogical agent realizations and the impact on learning enhancement.